Hearing balance and communication jubilees exponents of the 'twenties': Théophile Bonet (1620–1689), the deaf author of 'De Aurium Affectibus'. (2nd January 2020) - Mion, Marta
Abstract: Purpose: To discover the widest collection of anatomo-pathological findings published in the XVII century, Theophile Bonet's Sepulchretum sive Anatomia Practica (1679), the forerunner of Morgagni's De Sedibus et Causis Morborum (1761). Particular attention has been paid to the paragraphs relating to otology and audiology. Method: Section 19 of Book I of the Sepulchretum (entitled De Aurium Affectibus ) contains the description of all the ears pathologies found during autopsies performed at that time. Results: The annotations in this section provide an idea of the concepts and the knowledge that physicians had of otological and audiological syndromes in the XVII century. Conclusion: The Sepulchretum was fundamental in the development of modern medicine, as demonstrated by the similar treaties that followed Bonet's work.